Genetic diversity of Mycobacterium leprae in the state of São Paulo, an area of low-leprosy incidence in Brazil - Finardi, Amanda Juliane [UNESP]; de Oliveira, Nathan Guilherme [UNESP]; de Moraes, Eloise Brasil [UNESP]; Batista, Lavínia Cássia Ferreira [UNESP]; Bortolomai, Bruna Eduarda [UNESP]; Suffys, Philip Noel; Baptista, Ida Maria Foschiani Dias [UNESP] (FapUNIFESP (SciELO), 2023)
Background: Brazil has the second largest number of leprosy cases worldwide, and the state of São Paulo has been considered non-endemic since 2006. Methods: We analyzed 16 variable number tandem repeats loci and three single nucleotide polymorphisms loci of Mycobacterium leprae (M. leprae) in 125 clinical isolates from patients in different municipalities in the state. Results: The clustering pattern of M. leprae indicated that the transmission of leprosy persisted in the state and included scenarios of intra-extra-familial transmission in areas with low endemicity. Conclusions: A significantly active circulation of M. leprae was observed. Therefore, surveillance and control measures must be implemented.
Keywords: Genetic Diversity; Geographic Information System; Leprosy; Mycobacterium leprae; Transmission